Incentivising public transport use for physical activity gain: process evaluation of the COVID-19 disrupted trips4health randomised controlled trial - K. A. Jose; M. J. Sharman; O. Stanesby; S. Greaves; A. J. Venn; L. Blizzard; A. Palmer; K. Cooper; J. Williams; V. J. Cleland (BMC, 2022)
Abstract Background Partnering with a public transport (PT) provider, state government, and local government, the single-blinded randomised controlled trial, trips4health, investigated the impact of PT use incentives on transport-related physical activity (PA) in Tasmania, Australia. The intervention involved 16-weeks of incentives (bus trip credits) for achieving weekly PT use targets, supported by weekly text messages. This study objective was to conduct a process evaluation of the COVID-19 disrupted trips4health study. Methods The Medical Research Council UK's framework for complex public health interventions guided the process evaluation. Participant reach, acceptability, fidelity and feasibility were evaluated. Administrative and post-intervention survey data were analysed descriptively. Semi-structured interviews with intervention participants (n = 7) and PT provider staff (n = 4) were analysed thematically. Results Due to COVID-19, trips4health was placed on hold (March 2020) then stopped (May 2020) as social restrictions impacted PT use. At study cessation, 116 participants (approximately one third of target sample) had completed baseline measures, 110 were randomised, and 64 (n = 29 in the intervention group; n = 35 in the control group) completed post-intervention measures. Participants were 18 - 80 years (average 44.5 years) with females (69%) and those with tertiary education (55%) over-represented. The intervention was delivered with high fidelity with 96% of bus trip credits and 99% of behavioural text messages sent as intended. Interviewed PT staff said implementation was highly feasible. Intervention participant acceptability was high with 90% reporting bus trip incentives were helpful and 59% reporting the incentives motivated them to use PT more. From a total of 666 possible bus trip targets, 56% were met with 38% of intervention participants agreeing and 41% disagreeing that 'Meeting the bus trip targets was easy'. Interviews and open-ended survey responses from intervention participants revealed incentives motivated bus use but social (e.g., household member commitments) and systemic (e.g., bus availability) factors made meeting bus trip targets challenging. Conclusions trips4health demonstrated good acceptability and strong fidelity and feasibility. Future intervention studies incentivising PT use will need to ensure a broader demographic is reached and include more supports to meet PT targets. Trial registration ACTRN12619001136190 .